SAT0050 Early response to certolizumab pegol in rheumatoid arthritis predicts outcome: data from a prospective observational study. (15th June 2017) - Saraux, A; Flipo, RM; Fagnani, F; Massol, J; Combe, B; Huot-Marchand, P; Joubert, JM; Dunkel, J; Cukierman, G
Abstract : Background: Treat-to-target strategies for rheumatoid arthritis (RA) require reliable clinical markers of treatment response in order to adapt therapy. Markers of early treatment failure can be used to ensure that patients (pts) are not unnecessarily exposed to ineffective therapy. Data from interventional clinical trials suggest that early clinical measures of disease activity (such as CDAI, DAS28 or HAQ-DI) after 12 weeks (wks) of treatment can reliably predict treatment failure at 1 year (yr). 1–3 However, it is unknown how such indicators perform in real-world settings. Objectives: To evaluate the performance of clinical markers of early treatment failure (Wk12) as predictors of treatment failure at 1yr in everyday clinical practice. Methods: Data from a 1yr interim analysis of the ECLAIR study were used: a longitudinal, prospective, observational, multicentre study of pts with RA starting treatment with certolizumab pegol (CZP) in France. Pts were evaluated at study entry and thereafter at 3-monthly routine consultations. Disease activity was assessed at each visit using CDAI, DAS28 and HAQ-DI. At Wk12, pts with missing data or no longer taking CZP were excluded from the analyses. Linear interpolation, LOCF or NRI were used to impute missing data at 1yr, including data from pts who left the study early. Different definitions for treatment non-response were applied based on CDAI or ΔDAS28 and ΔHAQ-DI relative to pre-treatment values. Non-response at Wk12 was defined as CDAI>10, ΔDAS28<1.2 or ΔHAQ-DI<0.22. Then, failure at 1yr was defined as CDAI>22, DAS28>3.2 and HAQ-DI>0.5. Positive predictive values (PPV; proportion of treatment failures at 1yr in Wk12 non-responders) were used to evaluate the predictive performance of each tool. Results: Overall, 792 pts were enrolled and data from 730 pts analysed. Performance of CDAI at predicting treatment failure at 1yr was assessed in 532 pts (198 data values missing at Wk12). Response and failure rates at Wk12 and 1yr are presented (see Table). The PPV for CDAI was 88.8%, indicating that almost 9/10 pts identified as non-responders at Wk12 fail to respond at 1yr. Specificity was also high (96.0%), indicating that <5% of pts who achieved CDAI response at 1yr were non-responders at Wk12. Similar analyses performed for DAS28 and HAQ-DI produced PPVs of 69.0% and 75.4%, respectively. Conclusions: The PPV describing the performance of early CDAI measure as a predictor of treatment failure at 1yr among CZP-treated RA pts was high; 88.8% of pts identified as non-responders at Wk12 will represent a treatment failure at 1yr. Simple tools such as CDAI, assessed during routine consultations, may be reliable markers to predict treatment failure without need for complementary biological tests. References: Keystone EC. J Rheumatol 2011;38:990–6. Curtis JR. Arth Care Res 2012;64:658–67. van der Heijde D. J Rheumatol 2012;39:1326–33. Acknowledgements: This study was funded by UCB Pharma. We thank the patients and their caregivers in addition to the investigators and their teams who contributed to this study. We also thank Isabelle Bru (UCB Pharma) who helped conduct the ECLAIR study. Editorial services were provided by Costello Medical Consulting. Disclosure of Interest: A. Saraux Consultant for: UCB Pharma, R. M. Flipo Consultant for: UCB Pharma, F. Fagnani Consultant for: UCB Pharma, J. Massol: None declared, B. Combe Grant/research support from: Merck Pfizer Inc, Roche-Chugai, Consultant for: Merck, Pfizer, Roche-Chugai, UCB Pharma, Bristol-Myers Squibb, Celgene, Eli Lilly, Speakers bureau: Merck, Pfizer, Roche-Chugai, UCB Pharma, Bristol-Myers Squibb, Celgene, Eli Lilly, Novartis, P. Huot-Marchand: None declared, J. M. Joubert Employee of: UCB Pharma, J. Dunkel Employee of: UCB Pharma, G. Cukierman Employee of: UCB Pharma